A Study on Broiler Farming Practices Followed by the Farmers in Mizoram - Sailo, Lalruatfela; Das, Samares Kumar (International Journal of Bio-resource and Stress Management, 2018)
Broiler farming practices followed by the broiler farmers in Mizoram were studied to help R&D professionals take measures to improve the situation. From eight districts in Mizoram two (Aizawl and Kolasib), from each district two blocks and from each block five villages were selected purposively having maximum number of broiler farms, and from each village five farmers engaged in broiler farming were selected randomly to have a total of 100 respondents who were interviewed using a pre-tested semi-structured interview schedule. With a medium flock size (300-1,000, 66%) they purchased feed mainly from the feed dealer (41%) 3,200-16,000 kg feed (57%) spending Rs. 95,000-4,80,000 (53%) in a year they housed their birds intensively (69%). Cleaning the poultry houses by sweeping and washing with plain water 39% buried the dead birds. Treating the birds mainly by themselves (63%) farmers vaccinated their flocks against IBD (47%) and ND (30%) with little concern about the vaccination schedule. With an average Rs. 45 per chick, Rs. 150 per kg live bird and Rs. 38 per kg feed farmers sold their birds at 3 months weighing 3 kg majority (54%) sold their birds in the village. Measures should be taken to make the farmers aware of the need for vaccination on time and the need for adopting a scientific system of rearing. Marketing and veterinary services should be provided to improve the situation.